Orality Markers in Spanish Native and Dubbed Sitcoms: Pretended Spontaneity and Prefabricated Orality - Baños, Rocío (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
This article reflects on the divergences between translated and non-translated texts, and the specificities of fictional dialogue in audiovisual texts. Research suggests that audiovisual dialogue consists of a combination of linguistic features used in speech and writing, and that both translators and scriptwriters should aim to achieve a balance of these features to create spontaneous-sounding dialogues. Working with an audiovisual corpus of domestic and dubbed sitcoms in Spanish (Siete Vidas and Friends respectively), the purpose of this article is to provide an overview of how Spanish dialogues are shaped from a linguistic point of view across all language levels, highlighting the trends identified in their production and their translation in order to compare them. The results reveal the complex relationship established between speech and writing in audiovisual texts, and disclose the resources used by translators and scriptwriters to carefully plan dialogues which sound credible. Findings also suggest that domestic audiovisual texts bear more resemblance to spontaneous conversation than dubbed texts.